Boundary layer flow over a moving plate - Wee, Maurice Hong Jie (2014)
The content of this report covers a numerical study of boundary layer flow over a moving plate. The main aim of the study is to investigate heat transfer to and from a moving surface. The governing equations for the system were modeled through mathematical manipulation of existing known equations relating to heat transfer and boundary layer flow. The modeled governing equations were then solved with the use of “MATLAB”, a high-level language and interactive environment for numerical computation, visualization and programming.